Teacher's Efforts to Introduce Letters to Early Childhood at PAUD Al-Fikri, Seluma Regency - Nengsih, I.Y.Nengsih; Imran , R.F.; Haryono , Mimpira; Mesterjon, Mesterjon; Sari , R.P. (Jurnal Pendidikan Rafflesia, 2022)
The purpose of this study was to describe the teacher's efforts to introduce letters in PAUD Al-Fikri Seluma Regency. The methodology in this study uses a qualitative descriptive method. The results of the study show that the teacher's efforts to introduce letters to children are by determining learning strategies, the media used to introduce letters such as educational game tools, alphabet textbooks, or through playing while singing. So the teacher's efforts to introduce letters in PAUD Al-Fikri have been very innovative.